Tumor Volume Change With Stereotactic Body Radiotherapy (SBRT) for Early-stage Lung Cancer. (February 2015) - Bhatt, Aashish D.; El-Ghamry, Moataz N.; Dunlap, Neal E.; Bhatt, Geetika; Harkenrider, Matthew M.; Schuler, John C.; Zacarias, Albert; Civelek, Ali Cahid; Pan, Jianmin; Rai, Shesh N.; Woo, Shiao Y.
<x xml:space="preserve">Abstract</x> Objectives: To quantify gross tumor volume (GTV) change during stereotactic body radiotherapy (SBRT) and on first follow-up, as well as to evaluate for any predictive prognostic risk factors related to GTV decrease. An attempt was also made to identify the potential timing for adaptive SBRT. Methods: Twenty-five tumors in 24 consecutive patients were treated with SBRT to total dose of 50 Gy in 5 fractions. Median age was 72.5 years. Tumor stage was T1, 68%; T2, 20%; and other, 12%. The GTVs of on the 5 cone-beam computed tomographies (CBCT1-5) obtained before each fraction and the first follow-up CT (CTPOST) were analyzed. Results: Median time from diagnosis to initiation of radiotherapy was 64 days. GTV on CBCT1 was the baseline for comparison. GTV decreased by a mean of 7% on CBCT2 (P=0.148), 11% on CBCT3 (P=0.364), 19% on CBCT4 (P=0.0021), and 32% on CBCT5 (P=0.0004). Univariate analyses of GTV shrinkage was significantly associated with "time from CBCT5 to CTPOST" (P=0.027) and "T-stage" (P=0.002). In multivariate analyses, "T-stage" remained significant with T1 tumors showing greater GTV shrinkage than T2 tumors. Conclusions: Significant decrease in GTV volume based on daily CBCT was demonstrated during SBRT treatment. Adaptive SBRT has the potential to minimize integral dose to the surrounding normal tissues without compromising GTV coverage.